James R. Mann papers - Mann, James R. (James Robert), 1856-1922.
Correspondence, newspaper clippings, printed matter, memorabilia, and other papers relating to Mann's career in Chicago politics and as U.S. representative from Illinois. Subjects include Chicago River improvement, the Food and Drugs Act of 1906, interstate commerce legislation, the Mann Act of 1910 prohibiting interstate sex trafficking, investigation of the wood-pulp and paper industries by a congressional committee (1908-1910), Republican congressional party leadership, and Mann's political campaigns. Correspondents include John Norris, William Howard Taft, and James Wilson.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Lawyer and U.S. representative from Illinois.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Norris, John -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Wilson, James, -- 1835-1920 -- Correspondence; United States; United States; United States. -- Congress. -- House; Republican Party (U.S. : 1854- ); Drugs -- Law and legislation -- United States; Food law and legislation -- United States; Human trafficking -- Law and legislation -- United States; Interstate commerce -- Law and legislation -- United States; Paper industry -- United States; Political campaigns -- United States; Slavery -- Law and legislation -- United States; Wood-pulp industry -- United States; Chicago (Ill.) -- Politics and government; Chicago River (Ill.) -- History; Illinois -- Politics and government; United States -- Politics and government -- 1865-1933.; Lawyers; Representatives, U.S. Congress -- Illinois